Fine Needle Aspiration versus Fine Needle Capillary Sampling Technique in Cyto-diagnosis of Thyroid Lesions - Tiwari, Archana; Dahal, Prahar; Regmi, Sudeep; Rai, Ramji (Journal of Lumbini Medical College, 2020)
Introduction: In diagnosis of thyroid lesions, the negative pressure applied during fine needle aspiration cytology (FNAC) frequently produces bloody smears. This results in a compromise in cellular concentration and architecture which may lead to improper interpretation. Fine needle capillary sampling cytology (FNCC), on the other hand, avoids active aspiration as it depends on capillary tension to collect tissue samples in the needle bore. This study evaluated the diagnostic performance of FNAC and FNCC in thyroid lesions. Methods: A total of 120 patients were included in this study conducted over a duration of 19 months. All thyroid swellings advised for cyto-diagnosis were sampled by both fine-needle aspiration (FNAC) and non-aspiration (FNCC) techniques. The slides were assessed according to the Mair et al. scoring system. Results: In the FNCC group, 72 (60%) smears were diagnostically superior while 54 (45%) smears were diagnostically superior in the FNAC group. Blood contamination (p=0.003), cellular trauma (p=0.019), and degree of cellular degeneration (p=0.026) were less and cellular architecture (p=0.047) was preserved more in FNCC in comparison to FNAC groups. Conclusion: This study showed the superiority of FNCC for the interpretation and diagnosis of thyroid lesions. However, the combination of both FNAC and FNCC could maximize the diagnostic yield.